1981
DOI: 10.1590/s0074-02761981000100009
|View full text |Cite
|
Sign up to set email alerts
|

Cross-suppression of specific immune responses after oral tolerance

Abstract: Adult normal inbred mice rendered tolerant to OVA by previous oral exposure do not respond to intraperitonela immunization with DNP-OVA in adjuvant. These tolerant mice also form less DNP-specific antibodies to DNP-KLH when immunized with mixtures of DNP-KLH and DNP-OVA, or less HGG-specific antibodies when immunized with cross-linked conjugates of OVA and HGG. These same procedures increased DNP-specific or HGG-specific responses in non-tolerant control mice. The cross-supperssion was ineffective, however, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…However, we [27][28][29][30] and others [34][35][36] have demonstrated that injection of a tolerated antigen results in inhibition of antibody response to a second unrelated antigen injected simultaneously. We have called this phenomenon indirect effects of the exposure to tolerated proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we [27][28][29][30] and others [34][35][36] have demonstrated that injection of a tolerated antigen results in inhibition of antibody response to a second unrelated antigen injected simultaneously. We have called this phenomenon indirect effects of the exposure to tolerated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms are sometimes subtractive, such as clonal deletion [18,19] or anergy [16,20,21], and sometimes active, such as idiotypic interactions or T cell suppression mediated by suppressive cytokines [22][23][24][25][26][27]. Regardless of the explanation adopted, it is usually assumed that the tolerance is specific for the orally administered protein.…”
Section: Introductionmentioning
confidence: 99%
“…7 Oral tolerance induction to autoantigens is one of the possible treatments for Th1-mediated autoimmune diseases such as multiple sclerosis, 8,9 rheumatoid arthritis, 10,11 and type 1 diabetes. 12,13 Antigens administered orally enter the gut-associated lymphoid tissue (GALT), 14,15 which, as a primary function, protects the host from ingested pathogens and proteins. 16,17 Currently, 2 primary effector mechanisms of oral tolerance induction are known.…”
Section: Editorial P 1901 Clinical Perspective P 1976 Receptor (Ldlr)mentioning
confidence: 99%
“…8 Unexpectedly, parenteral re-exposure to a tolerated antigen was found to block the initiation of immune responses to a second unrelated antigen. [9][10][11] Thus, injection of a tolerated protein into orally tolerant mice inhibits immunological responses to unrelated proteins and block severe chronic inflammatory Gustavo C. Ramos, 1 reactions of immunological origin, such as autoimmune reactions and granulomatous lesions around Schistosoma mansoni eggs. 12 The mechanism proposed to explain this inhibitory effect was called 'bystander supression'.…”
Section: Introductionmentioning
confidence: 99%